Induction of Vascular Insulin Resistance, Endothelin-1 Expression and Acceleration of Atherosclerosis by the Overexpression of Protein Kinase C β Isoform in the Endothelium - Li, Qian (2013)
RATIONALE: Loss of insulin action on the endothelium can cause endothelial dysfunction and atherosclerosis. Hyperglycemia and elevated fatty acids induced by diabetes can activate protein kinase C (PKC) β isoforms and selectively inhibit insulin signaling via phosphatidylinositol 3-kinase (PI3K)/Akt pathway to inhibit the activation of endothelial nitric oxide synthase (eNOS) and metabolic actions. OBJECTIVE: To demonstrate that overexpressing PKCβ2 isoform in endothelial cells can cause selective insulin resistance and exacerbate atherosclerosis in the aorta. METHODS AND RESULTS: PKCβ2 isoform was overexpressed in endothelial cells using a promoter of vascular endothelial cell-cadherin (VE-Cadherin). These mice were cross-bred with ApoE(-/-) mice (Tg (Prkcb)ApoE(-/-)). On a Western diet, Tg(Prkcb)ApoE(-/-) and ApoE(-/-) mice did not differ in systemic insulin sensitivity, glucose tolerance, plasma lipid or blood pressure. Insulin action in endothelial cells and femoral artery from Tg(Prkcb)ApoE(-/-) mice were impaired by ∼40% with respect to Akt/eNOS activation and leukocyte-endothelial cell binding increased in cultured lung endothelial cells from Tg(Prkcb)ApoE(-/-)mice compared to ApoE(-/-) mice. Basal and angiotensin stimulated big endothelin-1 (ET-1) levels were elevated in Tg(Prkcb)ApoE(-/-) mice compared to ApoE(-/-) mice. The severity of atherosclerosis in the aorta from Tg(Prkcb)ApoE(-/-) mice increased by ∼70% as measured by en face fat staining and plaque content of the number of smooth muscle cells, macrophages and extracellular matrix. CONCLUSIONS: Specific PKCβ2 activation in the endothelial cells caused dysfunction and accelerated atherosclerosis due to loss of insulin-stimulated Akt/eNOS activation and angiotensin induced increases in ET-1 expression.